A Commitment to Public Office Ethics Reduces the Administrative Corruption Manifestation in Sudan - Zuly Qodir; Adil Hasan Ibrahim (Department of Government Studies Universitas Muhammadiyah Makassar, 2021)
This paper dealt with the issue of a commitment to the public office ethics reduces the administrative corruption manifestations in Sudan. The purpose of this paper is to find out what are the administrative corruption manifestations and how the commitment to the public office ethics contributes in the decreasing of administrative corruption forms. This paper depends on the literature review and uses descriptive approach in order to describe the forms of corruption which are related to the administration. Qualitative method has been followed in this work because, according to the view of the researcher, it is acceptable for this kind of study. The findings show that, embezzlement, extortion, exploitation of public position, forgery, deception, mediation, nepotism, favouritism and gifts to the public office are all shapes of administrative corruption that are pervasive in Sudan, Also, it indicates that, high levels of corporate transparency (auditing and reporting) and high Internet access can be beneficial in Sudan, that by combating corruption in the public sector and adopting effective policies to encourage the development of the private sector. Likewise, increase of salaries and wages for public sector workers can contribute in corruption reduction. The study recommends strongly to implement the principles of ethics of public offices, and law should be set in order to organize the bad morals of individuals in government agencies in Sudan.